Hydrogen Crossover in PEM and Alkaline Water Electrolysis: Mechanisms, Direct Comparison and Mitigation Strategies. Issue 7 (1st January 2018) - Trinke, P.; Haug, P.; Brauns, J.; Bensmann, B.; Hanke-Rauschenbach, R.; Turek, T.
Abstract : This study provides a direct comparison of hydrogen crossover in PEM (Nafion 117) and alkaline water electrolysis (Zirfon) at a temperature of 60 ∘ C applying state-of-the-art separating unit materials. To this end, occurring crossover mechanisms are described first, before experimental data of the anodic hydrogen content are shown in dependence of current density, system pressure and process management strategy. The results suggest that permeation in PEM electrolyzers is mainly governed by diffusion due to a supersaturated concentration of dissolved hydrogen within the catalyst layer, showing a share of 98} of the total permeation flux at 1 A cm − 2 and atmospheric pressure. Permeation in alkaline electrolyzers also exhibits a significant influence of supersaturation, but the overall crossover is mainly influenced by mixing the electrolyte cycles, which makes up a share of 90} at 0.7 A cm − 2 and 1 bar . Generally it becomes evident that hydrogen permeation across the separating unit is more than one order of magnitude smaller in alkaline electrolysis, which is mainly a consequence of the significantly lower hydrogen solubility in concentrated KOH electrolyte. Finally, this study concludes with an assessment of the impact of separating unit thickness and provides mitigation strategies to reduce hydrogen crossover.